2021
DOI: 10.3389/fneur.2021.779890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Glial Fibrillary Acidic Protein as a Potential Marker in Huntington's Disease

Abstract: Objective: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder. Neurofilament light protein (NfL) is correlated with clinical severity of HD but relative data are the lack in the Chinese population. Reactive astrocytes are related to HD pathology, which predicts their potential to be a biomarker in HD progression. Our aim was to discuss the role of blood glial fibrillary acidic protein (GFAP) to evaluate clinical severity in patients with HD.Methods: Fifty-seven HD mutation carriers (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Glial Fibrillary Acidic Protein (GFAP) and S100 proteins are both key markers of glial cells and play important roles in gliogenesis, the process of generating glial cells from neural progenitor cells [71].…”
Section: • Gfap and S100mentioning
confidence: 99%
See 1 more Smart Citation
“…Glial Fibrillary Acidic Protein (GFAP) and S100 proteins are both key markers of glial cells and play important roles in gliogenesis, the process of generating glial cells from neural progenitor cells [71].…”
Section: • Gfap and S100mentioning
confidence: 99%
“…Its expression is a hallmark of mature astrocytes, and it contributes to the structural integrity of these cells [72]. S100 proteins are a family of calcium-binding proteins that are predominantly found in glial cells, including astrocytes [73]. They play roles in cell cycle regulation, calcium homeostasis, and other intracellular processes.…”
Section: • Gfap and S100mentioning
confidence: 99%
“…Upregulation of the intermediate filament glial fibrillary acidic protein (GFAP) is essential for the transition of astrocytes to a reactive state ( 46 ). A recent study identified a significant elevation in plasma GFAP concentration in HD patients with the HTT mutation, suggesting its association with HD progression ( 47 ). Female mice were found to have significantly higher GFAP signals than males ( 48 , 49 ), indicating that female astrocytes may be more prone to inflammation than males in the context of HD.…”
Section: Sex Differences In Neuroinflammationmentioning
confidence: 99%